2022
DOI: 10.3390/ijerph19148405
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Cervicocephalic Kinesthetic Sensibility Measured during Dynamic Unpredictable Head Movements and Eye Movement Control or Postural Balance in Neck Pain Patients

Abstract: Cervical afferent input is believed to affect postural balance and oculomotor control in neck pain patients, but its relationship to cervicocephalic kinesthesia, describing movement sense, has not yet been studied. The aim of this study was to analyze the relationship of two aspects of cervicocephalic kinesthesia to postural balance and oculomotor control in neck torsion positions. Forty-three idiopathic neck pain patients referred from orthopedic outpatient clinics and forty-two asymptomatic controls were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…A study found that young patients with chronic neck pain had greater increases in postural sway with neck torsion compared to patients with unilateral vestibular loss and asymptomatic controls [ 9 ]. A recent study has also demonstrated the relationship between neck position sense and balance in the neck torsion maneuver [ 10 ], which supports a proposed mechanism of cervical-driven postural balance deficits. Thus, the neck torsion maneuver may further identify altered cervical afferent causes of impaired standing balance in older people with chronic neck pain.…”
Section: Introductionsupporting
confidence: 57%
“…A study found that young patients with chronic neck pain had greater increases in postural sway with neck torsion compared to patients with unilateral vestibular loss and asymptomatic controls [ 9 ]. A recent study has also demonstrated the relationship between neck position sense and balance in the neck torsion maneuver [ 10 ], which supports a proposed mechanism of cervical-driven postural balance deficits. Thus, the neck torsion maneuver may further identify altered cervical afferent causes of impaired standing balance in older people with chronic neck pain.…”
Section: Introductionsupporting
confidence: 57%
“…While position sense tests commonly apply parameters of variable, constant and absolute error 9 , 10 movement sense tests apply more diverse parameters such as smoothness of movement 11 , accuracy of head and neck movement 2 , 12 , 13 directional accuracy 14 , mean and peak velocity of head movement 12 , 13 , 15 time to peak velocity 12 , 16 and others, although all these are not consistently applied throughout the literature. Some studies apply limited amount of parameters 11 , 13 , 17 , while other studies apply numerous parameters simultaneously 18 20 which raises the concern of addressing different characteristics of kinaesthetic sensibility, however to our knowledge this has not yet been addressed.…”
Section: Introductionmentioning
confidence: 99%